Relationship between perceived material living conditions and subjective health and wellbeing as moderated by personal attributes in a representative sample of Nigerians - Dare A. Fagbenro; Dare A. Fagbenro; Erhabor S. Idemudia; Klaus Boehnke (Frontiers in Psychology)
BackgroundPrevious research has linked material living conditions to subjective health and wellbeing. However, moderators are mainly unknown. Thus, the current study examined whether gender, age, and education moderate Nigerians’ subjective health and wellbeing, considering their material living conditions.MethodsThe 2023 Afrobarometer survey in Nigeria’s six geopolitical zones included 1,600 adults aged 18–97 (Mean age = 34.93 years, standard deviation = 13.12, female = 51.9%). IBM SPSS Amos 23 performed SEM and multi-group analyses.ResultsThe study found that insufficient material living conditions harm subjective health and wellbeing. It revealed that such conditions harmed subjective health and wellbeing, regardless of age or gender. Surprisingly, education affected the relationship between material living conditions and subjective health and wellbeing, particularly among highly educated individuals.ConclusionThe study concluded that poor living conditions harm health and wellbeing, whereas education moderates the relationship between material living conditions and subjective health and wellbeing. These findings highlight the need for psychological interventions and policies to improve Africans’ health and wellbeing.